2023
DOI: 10.1371/journal.pbio.3002017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the m6A methyltransferase METTL3 in monocyte-derived macrophages ameliorates Alzheimer’s disease pathology in mice

Abstract: Alzheimer’s disease (AD) is a heterogeneous disease with complex clinicopathological characteristics. To date, the role of m6A RNA methylation in monocyte-derived macrophages involved in the progression of AD is unknown. In our study, we found that methyltransferase-like 3 (METTL3) deficiency in monocyte-derived macrophages improved cognitive function in an amyloid beta (Aβ)-induced AD mouse model. The mechanistic study showed that that METTL3 ablation attenuated the m6A modification in DNA methyltransferase 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Such results are consistent with emerging studies showing that m 6 A regulates inflammation, macrophages and also astrocytosis [57][58][59][60][61]. Such findings raise the possibility that m 6 A modulation might also be applied towards regulation of inflammation in AD; indeed a recent study observed that conditional knockout of METTL3 in microglia attenuated inflammation and A accumulation in a mouse model based on A injection [62].…”
Section: Discussionsupporting
confidence: 89%
“…Such results are consistent with emerging studies showing that m 6 A regulates inflammation, macrophages and also astrocytosis [57][58][59][60][61]. Such findings raise the possibility that m 6 A modulation might also be applied towards regulation of inflammation in AD; indeed a recent study observed that conditional knockout of METTL3 in microglia attenuated inflammation and A accumulation in a mouse model based on A injection [62].…”
Section: Discussionsupporting
confidence: 89%
“…These findings indicate that the aberrant expression and distribution of METTL3 in the hippocampus of the AD brain may represent an epi transcriptomic mechanism for the pathogenesis of AD [ 46 ]. Similarly, Yin et al reported that METTL3 downregulation in monocyte-derived macrophages improved cognitive function in an amyloid beta (Aβ)-induced AD mouse model [ 47 ]. Mechanistically, METTL3 downregulation reduced m6A modification in DNA methyltransferase 3A (DNMT3A) mRNAs and consistently inhibited YTHDF1-mediated DNMT3A translation.…”
Section: Mettl3 In Neuropathological Eventsmentioning
confidence: 99%
“…Mechanistically, METTL3 downregulation reduced m6A modification in DNA methyltransferase 3A (DNMT3A) mRNAs and consistently inhibited YTHDF1-mediated DNMT3A translation. In addition, DNMT3A bound to the promoter region of alpha-tubulin acetyltransferase 1 (ATAT1) and maintained its expression [ 47 ]. Therefore, METTL3 depletion resulted in the downregulation of ATAT1, reduced acetylation of α-tubulin, and subsequently enhanced migration of monocyte-derived macrophages and Aβ clearance [ 47 ].…”
Section: Mettl3 In Neuropathological Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective METTL3 in blood-derived macrophages reduced DNA methyltransferase 3A ( Dnmt3a ) translation in a YTHDF1-dependent manner, downregulating α-tubulin acetylation due to decreased α-tubulin acetyltransferase 1 ( Atat1 ) expression. METTL3 deficiency improved cognitive function in an amyloid β (Aβ)-induced Alzheimer’s disease mouse model by enhancing macrophage migration and Aβ clearance [54].…”
Section: M6a Modification In Monocytes/macrophagesmentioning
confidence: 99%